A quantum-trace determinantal formula for matrix commutators, and applications - Khurana, Dinesh (Elsevier, 2012)
In this paper, we establish a determinantal formula for 2×2 matrix commutators [X,Y]=XY-YX over a commutative ring, using (among other invariants) the quantum traces of X and Y. Special forms of this determinantal formula include a "trace version", and a "supertrace version". Some applications of these formulas are given to the study of value sets of binary quadratic forms, the factorization of 2×2 integral matrices, and the solution of certain simultaneous diophantine equations over commutative rings.
Only IISERM authors are available in the record.
Keywords: Binary quadratic forms; Determinants; Diophantine equations; Matrix commutators